2003
DOI: 10.1021/ja0275717
|View full text |Cite
|
Sign up to set email alerts
|

19F MAS NMR Quantification of Accessible Hydroxyl Sites on Fiberglass Surfaces

Abstract: Solid-state 19F nuclear magnetic resonance (NMR) spectroscopy is used for the quantitative investigation of accessible hydroxyl sites on low surface area glass fibers. Samples with surface areas as low as 0.2 m2/g are investigated through covalent binding of (3,3,3-trifluoropropyl)dimethylchlorosilane. 19F is an ideal nucleus for solid-state NMR, as it has a nuclear spin of 1/2 and a natural isotopic abundance of 100%. High-speed MAS techniques (with rotor spinning frequencies greater than 15 kHz) sufficiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 11 publications
1
60
0
Order By: Relevance
“…The number of reactive hydroxyls per gram is referred to as the specific hydroxyl number. Previously, we have used this method to quantify the number of hydroxyls that react with TFS (n TFS ) for fiberglass, volcanic glasses, and clay minerals (Fry et al, 2003;Washton et al, 2008;Sanders et al, 2010). For kaolinite surfaces, we demonstrated that TFS binds exclusively to edge sites and that our reactive surface site quantification was proportional to AFM edge surface area measurements (Sanders et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The number of reactive hydroxyls per gram is referred to as the specific hydroxyl number. Previously, we have used this method to quantify the number of hydroxyls that react with TFS (n TFS ) for fiberglass, volcanic glasses, and clay minerals (Fry et al, 2003;Washton et al, 2008;Sanders et al, 2010). For kaolinite surfaces, we demonstrated that TFS binds exclusively to edge sites and that our reactive surface site quantification was proportional to AFM edge surface area measurements (Sanders et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…After stopping dissolution at each time point for reactors prepared and then removed in duplicate, solid samples were TFS-treated in duplicate for 19 F MAS NMR analysis to quantify A reactive via a previously published method (Fry et al, 2003;Washton et al, 2008;Sanders et al, 2010). This protocol provided for an averaging of four values for each time point.…”
Section: Surface Modification and Nmr Experimentsmentioning
confidence: 99%
“…Some research into the surface of E-glass has been published, but a greater volume on pure silica exists in the literature. This is a useful place to begin the discussion, as the complexities introduced by adding or altering even one component in a silica or glass system can significantly alter its state and complicate analysis of the surface [70,71]. The study of pure silica systems began many decades ago [72] and has continued since [71,73,74].…”
Section: Hydroxyl Groupsmentioning
confidence: 99%
“…A similar value of between 4.2 and 5.4 nm´2 was also reported by Bakaev and Pantano [74] using a hydrogen/deuterium exchange method. The Kiselev-Zhuravlev constant appears to be generally accepted; however, differing values for fully-hydroxylated silica have been reported; for example, α OH = 1.3 nm´2 [71] and α OH = 8.2-9.8 nm´2 [73]. Significant differences in the materials and methods for which these values were obtained may explain the disagreement in α OH values.…”
Section: Hydroxyl Groupsmentioning
confidence: 99%
“…We have previously shown that a sensitive and chemically direct measure of hydroxyl reactivity for low surface area oxides is obtainable through the chemical process of silanization (Fry et al, 2003b), a surface modification technique long used in the chromatographic industry to couple molecules with desired functionality to high surface area materials (Van-Der-Voort and Vansant, 1996;Nawrocki, 1997). Although silane coupling to oxides has typically been utilized to modify the surface hydrophilicity, such modification often entails condensation of tri-functional organosilanes that can react with more than one surface hydroxyl while also generating a cross-linked polymeric structure near the surface via silane-silane reactions.…”
Section: Introductionmentioning
confidence: 99%